Effect of COVID-19 Pandemic Process on Student Behavior - Tarlakazan, Elif; Tarlakazan, Burak Erhan (Gazi Üniversitesi, 2020)
The COVID-19 pandemic has developed as a process that directs the whole world to take various measures at an unexpected time. In this process, internet access and electronic media, which are increasingly taking place in human life, have caused social life to move to this platform. As a result of this new situation; communication, gaming, shopping, education, etc. needs have been moved to virtual environments. The research was carried out by Kastamonu University, Faculty of Fine Arts and Design, Department of Graphic Designt to reveal changes in student behavior (eating and drinking, technology use, etc.) before and during the COVID-19 pandemic. Research data; It was collected from 93 students enrolled in the graphic design department, who voluntarily participated in the study, using a computer-aided online survey method. In this context, an ethical decision was made to be made by the Scientific Research and Publication Board of Kastamonu University, dated 25/03/2021 and numbered 70. The research findings; While there is no change in the use of social media by university students in the COVID-19 process, the rate of communicating with friends and participating in various social activities is very low. In addition, while the consumption of snacks decreased, the consumption of home-cooked meals increased, and a significant difference was observed in the ratio of studying, watching movies, and reading books.

COVID-19 pandemisi tüm dünyayı hiç beklemediği bir anda çeşitli tedbirler almaya yönelten bir süreç olarak gelişmiştir. Bu süreçte insan yaşantısında internet erişimi ve elektronik ortamlar giderek daha fazla yer tutmuştur. Süreç sosyal yaşamın da bu platforma taşınmasına sebep olmuştur. Bu yeni durum neticesinde; iletişim, oyun, alışveriş, eğitim vb. ihtiyaçlar sanal ortamlara taşınmıştır. Araştırma Kastamonu Üniversitesi, Güzel Sanatlar ve Tasarım Fakültesi, Grafik Tasarımı Bölümü öğrencileri özelinde yürütülmüştür. Araştırma COVID-19 pandemisi öncesi ve sürecinde öğrenci davranışlarındaki (yeme-içme, teknoloji kullanımı vb) değişimleri ortaya koymak amacıyla yürütülmüştür. Araştırma verileri; çalışmaya gönüllü olarak katılan, grafik tasarımı bölümüne kayıtlı 93 öğrenciden, bilgisayar destekli çevrimiçi anket yöntemiyle toplanmıştır. Bu kapsamda Kastamonu Üniveritesi Bilimsel Araştırma ve Yayın Etiği Kurulunun 25/03/2021 tarih ve 70 nolu kararınca araştırma yapılması için etik kurul kararı alınmıştır. Araştırma bulgularına göre; COVID-19 sürecinde üniversite öğrencilerinin sosyal medya kullanımlarında bir değişiklik gözlenmezken, arkadaşlarıyla iletişim kurma, çeşitli sosyal aktivitelere katılma oranları düştüğü gözlenmektedir. Ayrıca bu süreçte atıştırmalık ürün tüketimi azalırken ev yemekleri tüketimi artmış, ders çalışma, film izleme, kitap okuma oranında da anlamlı oranda artış gözlenmiştir.
Keywords: Alan Eğitimleri; Other Fields of Education; COVID-19; Behavior change; Habit; Remote access; Graphic design; Covid-19; Davranış değişikliği; Alışkanlık; Uzaktan erişim; Grafik tasarım